Kedudukan Pendaftaran Tanah Dalam Peralihan Suatu Hak Atas Tanah - Alfarizi, Akmal Yogi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The purpose of this study is about the position of land registration in the transfer of land rights. The research method used is the normative juridical method. Where this research focuses on laws and regulations, books, and other related literature. Land registration is a very fundamental thing in land matters, it is the starting point in the orderly administration that must be carried out by authorized officials and the community in making applications. The land registration system in Indonesia in fact uses a negative registration publication system to make an impact that results in the government not guaranteeing the correctness of the data presented in certificates and land books. Indonesia must adhere to a negative land registration publication system with positive ententions so that data and a transitional event have certainty and are guaranteed legal protection.